Communication-as-Control: Intent-Aware Interaction for Scalable Multi-Agent Coordination - Imani, Mahdi; Lan, Tian (Proceedings of the AAAI Symposium Series, 2026)
Uncrewed Aerial Systems (UAS) increasingly operate aslarge, heterogeneous teams under partial observability. Insuch settings, coordination depends on how agents infer,represent, and act upon uncertainty about one another:belief divergence is a natural consequence of asymmetricsensing and latent intent, and naive communicationmechanisms do not scale with team size. We argue for areframing of interaction as communication-as-control,grounded in a small set of tightly coupled capabilitiesthat link sensing to distributed execution underinteraction constraints. Rather than prescribing a fixedpipeline, coordination in such teams relies on severalinterdependent capabilities. First, agents must performimplicit intent inference without communication, forminguncertainty-aware beliefs over teammate intent and progressfrom observable behavior. Second, such uncertainty caninform selective explicit interaction, with targeted,minimal exchanges invoked only when unresolved ambiguitybecomes consequential for joint decision-making. Third,uncertainty arising from both implicit inference andexplicit interaction can be leveraged to supportbelief-guided coordination and adaptation when alignment ispartial, delayed, or unattainable. This makes selectiveinteraction a scalability mechanism: as teams grow in sizeand heterogeneity, coordination remains feasible only ifcommunication is sparse, recipient-specific, and tied todecision relevance.